STUDI LITERATUR PERKEMBANGAN GREEN BUILDING DI INDONESIA - Kadek, Bayu Widiarsa; Kumara, INS; Sari Hartati, Rukmi (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
Green building is an alternative to anticipate damage to the earth due to development activities. This study reviews the development of green building inkIndonesia with a systematic literature method. The review that was carried out included regulations, implementation and implementation of green building in Indonesia. The development of government regulations on green buildings requires that every building meet the criteria of a green building. There are 20 buildings that have been certified green building by 2018 with the gold to platinum category. Research in the field of green building has also developed with 53 scientific publications. From the latest reviews, it is found that the implementation of green building in Indonesia has been carried out in various aspects of the building. In the future, policies and regulations at the national and regional levels are integrated with each other to implement green building comprehensively in Indonesia.